Supramolecular self-assembly of a hybrid 'hyalurosome' for targeted photothermal therapy in non-small cell lung cancer - Haipeng Xu; Lin Dong; Zhang Bin; Huo Yansong; Lin Shaofeng; Liu Chang; Chen Chen; Wang Changli (Taylor & Francis Group, 2020)
Despite the excellent efficacy and low toxicity of photoresponse therapy, which has attracted considerable attention for use in non-small cell lung cancer (NSCLC) therapy, unsatisfactory cellular permeability, and instability, both in vitro and in vivo have limited further clinical applications of indole cyanine photosensitizers. Here, we explore the supramolecular self-assembly of a 'hyalurosome' that is mediated by calcium phosphate nanonuclei. Through hyaluronate-mediated CD44 targeting, the constructed hyalurosome specifically delivers ICG into NSCLC cells and then induces severe hyperthermia accompanied by the generation of singlet oxygen upon photoirradiation. In contrast to the action of the native form, indocyanine green encapsulated in a hyalurosome showed significantly increased cellular endocytosis and inhibited cell proliferation both in vitro and in vivo. Our study indicated that this hyalurosome is a promising candidate for the targeted delivery of photosensitizers, which may be useful in NSCLC therapy.